THE EFFECT OF THERAPY GUIDED IMAGERY ON THE LEVEL OF ANXIETY IN PATIENTS OF TYPE 2 DIABETES MELLITUS - Susanti, Susanti; Ristyawati, Rizka Nur Indah (Nurse and Holistic Care, 2021)
Background: Type 2 diabetes mellitus (DM) is a chronic disease that has a negative physical and psychological impact. The psychological impact such as feeling useless and depressed. It causes a high level of anxiety, which makes a person vulnerable. Thus, it will complicate the management of type 2 diabetes mellitus. Objective: This study aims to analyze the effect of guided imagery therapy on the level of anxiety in patients with type 2 diabetes mellitus. Methods: This study used pre-experimental designs with one group pretest-posttest design with a sample of 26 respondents taken using simple random sampling technique. Measuring the level of anxiety using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data were analyzed using the Wilcoxon statistical test. Results: Data of respondents with DM who had anxiety before the guided imagery therapy in the mild anxiety level category were 21 people (81%), after the therapy decreased with the anticipation category as many as 21 people (81%).  Obtained p-value 0.000 with α = 0.05 (p < α), indicating that there is an effect of guided imagery therapy on anxiety levels in type 2 diabetes mellitus patients in Bulak Banteng Health Center Area. Conclusions: This study shows that applying guided imagery therapy can reduce anxiety levels in patient with type 2 diabetes mellitus. Researchers recommend that future researchers use more samples.